2021
DOI: 10.1371/journal.pone.0251419
|View full text |Cite
|
Sign up to set email alerts
|

Early exclusive breastfeeding cessation and postpartum depression: Assessing the mediating and moderating role of maternal stress and social support

Abstract: Background Early termination of exclusive breastfeeding (EBF) and postpartum depression (PPD) are both recognized as global health problems. Recent literature reviews demonstrate a notable link between PPD and breastfeeding outcomes, however, the underlying mechanisms linking the two remain unclear. Objectives The aim of the study is to: 1) explore the comparative risk for PPD among new mothers who terminated EBF before the 6-month mark, compared to those who did not; and 2) test whether maternal stress and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
2
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 78 publications
(117 reference statements)
1
22
2
7
Order By: Relevance
“…According to Toledo et al (9) and Gila-Diaz et al (10), women who currently breastfed their infants or breastfed them for a more extended time expressed significantly lower PPD risk. In line with this finding are the results from the study by Islam et al (11) that have pointed to the role of early cessation of exclusive breastfeeding for the increased risk of PPD. The mixed-feeding method might also be related to increased depression symptoms postpartum (12,13).…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…According to Toledo et al (9) and Gila-Diaz et al (10), women who currently breastfed their infants or breastfed them for a more extended time expressed significantly lower PPD risk. In line with this finding are the results from the study by Islam et al (11) that have pointed to the role of early cessation of exclusive breastfeeding for the increased risk of PPD. The mixed-feeding method might also be related to increased depression symptoms postpartum (12,13).…”
Section: Introductionsupporting
confidence: 73%
“…These results seem to differ from some of those published so far, which indicate that the infant feeding method may be related to a maternal mood where breastfeeding mothers are less depressed (9, 10) or formula feeding women have higher rates of depression than women who breastfeed (36). Islam et al (11) analysis show that non-exclusively breastfeeding mothers were more likely to experience depressive symptoms than exclusively breastfeeding mothers. Similarly, in the study conducted by Takashori (37), there was a significant difference in the prevalence of alleviated EPDS scores between breastfeeding and non-breastfeeding mothers (2.5 and 19.4%, respectively).…”
Section: Discussioncontrasting
confidence: 56%
“…Not engaging in breastfeeding reduces the attenuating cortisol stress response, a factor that is related to higher depressive symptoms [44]. This relationship is evidenced by a recent study that showed that mothers with early negative breastfeeding experiences were 7.58-fold more likely to suffer from postpartum depression [45]. Furthermore, Khalifa et al [46] demonstrated that an exclusive breastfeeding practice reduced the odds of postpartum depression by 80% among a sample of 300 Sudanese women.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with depression are no more or less likely to intend to breastfeed but are known to have earlier cessation 6. Breastfeeding complications and early cessation are also established risk factors for new postpartum depression among individuals without a history of depression 7. However, high levels of stress, low social support, and high anxiety are all associated with early cessation of exclusive breastfeeding and appear to mediate the relationship between breastfeeding patterns and postpartum mood disorders, suggesting that the social environment predicts both the breastfeeding practices and the mood symptoms 8–10.…”
Section: Introductionmentioning
confidence: 99%